USLUB THOLABI (TUNTUTAN) DALAM AL-QURâAN (Suatu Tinjauan Pragmatis) - Akla, Akla (STAIN Jurai Siwo Metro, 2004)
Al-Qurâan is the media for interaction between God and His creatures. As the interaction media, it uses various kinds of sentence. The sentences are categorized into two forms : tholabi and ghairu tholabi. The tholabi sentences are not always in the form of imperative sentences; there are other forms. In other words, the meaning of a verse is not always linear with its formal form. The pragmatic approach can be used to find the follow up function of the tholabi sentences.Â Keywords : Guidance, Pragmatis